The Orientation of Turjuman Al-Mustafid Tafsir as the Root of the Interpretation Tradition in the Nusantara - Mahaly, Muhammad Jalaludin Al (Jurnal Iman dan Spiritualitas, 2024)
The purpose of this study is to analyze the orientation of Turjuman al-Mustafid's interpretation as the root of interpretation in the Nusantara. The research method used is library research. Data is collected through observation and documentation and then analyzed using qualitative analysis. The results of this study show that the orientation of Tafsir Turjuman al-Mustafid's interpretation is in (1) Local Cultural Adaptation, especially in the use of Malay and Jawi letters. (2) Simple Language, with its clear and easy-to-digest language style, makes this interpretation accessible to various levels of society. (3) Emphasis on the Spiritual and Sufistic Dimensions, by teaching Sufism values such as patience, sincerity, and tawakal. (4) Integration with Islamic Classical Teachings, while remaining rooted in Islamic classical teachings, by referring to the Qur'an, hadith, and classical interpretations as the main interpretation sources. (5) Driving the Formation of Nusantara Islamic Identity, by combining local elements and Islamic teachings, this interpretation helps to strengthen the sense of ownership and pride in the distinctive Islamic identity of the Nusantara. (6) Da'wah and Education, which are used as a tool to spread Islamic teachings and deepen religious understanding among the Malay community. (7) Contextualization of the teachings of the Qur'an, as an effort to help bridge the gap between the text of the Qur'an and the context of daily life. This study implies that Tafsir Turjuman al-Mustafid is not just a work of interpretation, but also a symbol of the integration of Islam with local culture as well as efforts to strengthen and maintain Islamic identity in the Nusantara.